Myeloperoxidase is a potential molecular imaging and therapeutic target for the identification and stabilization of high-risk atherosclerotic plaque. (26th July 2018) - Rashid, Imran; Maghzal, Ghassan J; Chen, Yung-Chih; Cheng, David; Talib, Jihan; Newington, Darren; Ren, Minqin; Vajandar, Saumitra K; Searle, Amy; Maluenda, Ana; Lindstedt, Eva-Lotte; Jabbour, Andrew; et al.
Abstract: Aims: As the inflammatory enzyme myeloperoxidase (MPO) is abundant in ruptured human atherosclerotic plaques, we aimed to investigate the role of MPO as a potential diagnostic and therapeutic target for high-risk plaque. Methods and results: We employed the tandem stenosis model of atherosclerotic plaque instability in apolipoprotein E gene knockout ( Apoe −/− ) mice. To test the role of MPO, we used Mpo −/− Apoe −/− mice and the 2-thioxanthine MPO inhibitor AZM198. In vivo MPO activity was assessed by liquid chromatography-tandem mass spectrometry detection of 2-chloroethidium generation from hydroethidine and by bis -5HT-DTPA-Gd (MPO-Gd) molecular magnetic resonance imaging (MRI), while plaque phenotype was verified histologically. Myeloperoxidase activity was two-fold greater in plaque with unstable compared with stable phenotype. Genetic deletion of MPO significantly increased fibrous cap thickness, and decreased plaque fibrin and haemosiderin content in plaque with unstable phenotype. AZM198 inhibited MPO activity and it also increased fibrous cap thickness and decreased fibrin and haemosiderin in plaque with unstable phenotype, without affecting lesion monocytes and red blood cell markers or circulating leukocytes and lipids. MPO-Gd MRI demonstrated sustained enhancement of plaque with unstable phenotype on T1-weighted imaging that was two-fold greater than stable plaque and was significantly attenuated by both AZM198 treatment and deletion of the Mpo gene. Conclusion: Our data implicate MPO in atherosclerotic plaque instability and suggest that non-invasive imaging and pharmacological inhibition of plaque MPO activity hold promise for clinical translation in the management of high-risk coronary artery disease.